A robótica educacional e mediação: um olhar sobre a organização e a prática pedagógica do trabalho docente - Silva, Thiago Sousa da (2022)
Dissertation developed during the Professional Master's Degree in Teaching in Basic Education of Stricto Sensu Graduate Program of the Teaching and Research Applied to Education Center (CEPAE) of the Federal University of Goiás (UFG), between 2019 and 2022. In this research work, pedagogical mediation is the structuring element that enables thinking working with educational robotics within aspects such as teacher training, the role of technology in education and the possibilities for a more humanized approach to its use. Research is carried out on the relationship between pedagogical mediation and educational robotics, in order to investigate how the mediation process created by the teacher when integrating educational robotics in the teaching and learning process is constituted. Therefore, it is necessary to identify the teachers' pedagogical conception, identify the role of technology in education for them, and also analyze the mediation process thought by them in the use of educational robotics. Studies by Tardif (2011) and Freire (2019) are used for issues related to training and teaching knowledge; on the organization, objectives and planning of the pedagogical work, the productions of Libâneo (2011, 2013) are used; for the discussion on technology and its role in education we will use Peixoto (2016) and Vieira Pinto (2005); and for the discussions on mediation, studies by Vigotski (2007) were used. In its methodological aspects, two instruments were used, in a complementary way, the first being the literature review of studies involving educational robotics in Elementary Education, published in the period from2016 to 2020. The second was the instrument of semi-structured interviews with teachers of Education Fundamental that they use educational robotics in their educational practice. Given this, there is the presence of a pedagogical conception very concerned with the instrumental and technical aspects involved in teaching with educational robotics. Also, a difficulty on the part of teachers in understanding mediation without associating it with the methodological aspects of their classes, the presence of educational robotics in schools as a marketing tool for educational institutions. And finally, the realization that educational robotics is not yet something fully mastered by teachers, and that its current stage of use demonstrates the need for a long process of conceptual and practical appropriation by teachers, especially teachers in the Elementary School stage. Part of this research is the educational product entitled “TEACHING AND EDUCATIONAL ROBOTICS: A didactic-pedagogical proposal”, which is a didactic-pedagogical support text for Elementary School teachers.